STRUKTUR ORGANISASI PESANTREN SALAFI DI CIREBON STUDI ATAS PONDOK PESANTREN ASSUNNAH KALITANJUNG DAN PONDOK PESANTREN DHIYÄ€US SUNNAH DUKUH SEMAR CIREBON - Sahiron Syamsuddin, Muhammad Abdul Karim, Muhammad Ali, Heddy Shri Ahimsa-Putra (Arabic Letters and Department, 2016)
Salafi groups are very proscribe organizations, tandzim, and association. These are all heretics and can bring the Muslims to hizbiyya and harakiyya and keep them away from al-wala wa 'l-bara. Meanwhile, to establish friendship among Salafis, they usually conduct a study Islam together and visit each other. According to Salafi groups, it is more effective than setting up an organization that many madharat. In administering the program in pesantrens, various ustadhs appointed to occupy certain positions in themanagement structure so that the pesantren is running properly.